Comorbid infections in patients with spondyloarthritis: frequency, structure and risk factors - M. M. Baranova; N. V. Muravyeva; B. S. Belov; T. V. Korotaeva; S. I. Glukhova (Современная ревматология)
Objective: To investigate the frequency, structure, and risk factors of comorbid infections (CI) in patients with spondyloarthritis (SpA).Material and methods. The study included 332 patients with SpA. Patients were interviewed by the investigating physician, and additional information was obtained from medical records.Results and discussion. Respiratory tract (RT) and ear, nose, and throat (ENT) infections ranked first in the structure of CI. Exacerbation of SpA after CI was found in 42% of patients, and more severe CI against the background of SpA was found in 83 patients. 63 cases of severe CI (SCI) were documented, 63.5% of which were infections of the RT and ENT organs. Predictors for the development of lower RT (LRT) and ENT organ infections were the use of biologic disease-modifying antirheumatic drugs (bDMARDs) in general (odds ratio, OR 2.018; 95% confidence interval, CI 1.221-3.335; p=0.006 and OR 1.761; 95% CI 1.1-2.819, respectively; p=0.018) and tumor necrosis factor-α (TNF-α) inhibitors in particular (OR 2.376; 95% CI 1.417-3.983; p=0.001 and OR 1.833; 95% CI 1.123-2.994; p=0.015), and disease duration of more than 5 years (OR 1.774; 95% CI 1.034—3.042; p=0.037 and OR 2.22; 95% CI 1.378-3.576; p=0.001). The risk of developing LRT infection was higher in the presence of chronic lung disease (OR 3.673; 95% CI 1.602-8.425; p=0.002) and Charlesson Comorbidity Index ≥1 (OR 2.381; 95% CI 1.439-3.94; p=0.001), risk of developing ENT organ infections - with the use of >1 bDMARD (OR 2.4; 95% CI 1.199-4.804; p=0.013) and duration of methotrexate therapy over 5 years (OR 2.478; 95% CI 1.053-5.831; p=0.038). Risk factors for the development of SCI were the use of bDMARDs in general (OR 1.941; 95% CI 1.063-3.545; p=0.031) and TNFα in particular (OR 2.246; 95%, CI 1.218-4.139; p=0.01).Conclusion. The problem of CI in SpA is of great importance. The vast majority of patients with SpA should be vaccinated against pneumococcal infection and influenza.